Synthesis, conclusions and implications for institutional development and future research - Benchaphun Ekasingh (2018)
© 2007, Springer-Verlag Berlin Heidelberg. This chapter has revealed some of the institutional constraints hindering sustainable development in the mountainous regions of the two countries under study, Vietnam and Thailand. It provides many examples of how failure to achieve better institutional arrangements lead to shortfalls in sustainable development. The chapter goes into detail on particular aspects of institutions, namely land rights and tenure, rural financial markets, institutions for upland agricultural research and local administration.